2006
DOI: 10.1038/sj.bjc.6603302
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic alterations on the short arm of chromosome 11 are involved in a majority of sporadic Wilms' tumours

Abstract: Wilms' tumour is one of the most common solid tumours of childhood. 11p13 (WT1 locus) and 11p15.5 (WT2 locus) are known to have genetic or epigenetic aberrations in these tumours. In Wilms' tumours, mutation of the Wilms tumour 1 (WT1) gene at the WT1 locus has been reported, and the WT2 locus, comprising the two independent imprinted domains IGF2/H19 and KIP2/LIT1, can undergo maternal deletion or alterations associated with imprinting. Although these alterations have been identified in many studies, it is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…WTs that retain normal imprinting at 11p13 form a small group of tumors, which seem to have a distinct phenotype of high stage and relatively late age of onset (Table 1), although, clearly, this result needs replicating in a larger series. Overall therefore, these results show that LOI at the WT1 locus, associated with hypomethylation of the ARR DMR, is a frequent event in WT, in contrast to the very infrequent hypermethylation of the WT1 sense promoter reported in WT (30,31). Our results, together with previous reports of methylation changes at or close to the WT1 ARR in human breast cancer (32), acute myeloid leukemia (33), ovarian clear cell adenocarcinoma (34), and rat mesothelioma and renal cell carcinoma (35), pinpoint the WT1 ARR as a target for epigenetic deregulation in a range of cancers.…”
Section: Loi At 11p13mentioning
confidence: 50%
See 1 more Smart Citation
“…WTs that retain normal imprinting at 11p13 form a small group of tumors, which seem to have a distinct phenotype of high stage and relatively late age of onset (Table 1), although, clearly, this result needs replicating in a larger series. Overall therefore, these results show that LOI at the WT1 locus, associated with hypomethylation of the ARR DMR, is a frequent event in WT, in contrast to the very infrequent hypermethylation of the WT1 sense promoter reported in WT (30,31). Our results, together with previous reports of methylation changes at or close to the WT1 ARR in human breast cancer (32), acute myeloid leukemia (33), ovarian clear cell adenocarcinoma (34), and rat mesothelioma and renal cell carcinoma (35), pinpoint the WT1 ARR as a target for epigenetic deregulation in a range of cancers.…”
Section: Loi At 11p13mentioning
confidence: 50%
“…S5). Others have also shown that the Kv DMR is not often hypomethylated in non-LOH WTs but is hypomethylated in heterozygous tumors (30,41). Thus, a possible explanation for the late-onset phenotype in 11p15 LOI WTs might be that they lack the alerted expression of imprinted genes in the IC2 domain such as CDKN1C that should occur in 11p15 LOH WTs.…”
Section: Loi At 11p15mentioning
confidence: 99%
“…Combined bisulfite restriction analyses (COBRA) using the hot-stop method were employed as described previously. 3,4 For H19-DMR, bisulfite sequencing was performed using the same primers as used for COBRA. PCR primers and conditions are shown in Supplementary Table 1.…”
Section: Methylation Analysesmentioning
confidence: 99%
“…Because the acquired chromosome 11p15.5 deletion is frequently observed in a variety of malignancies, 8 and acquired deletion of the HBB gene is also described by Badens and by Galanello et al, 9,10 we suspected that the patient may have a hemizygosity caused by acquired deletion of chromosome 11p15.5 harboring the HBB gene. However, FISH analysis showed that both chromosome 11s had positive hybridization signals with all three probes studied (β-LCR, HBG and HBB gene probes), indicating that the HBB gene cluster was probably intact ( Figure 1B).…”
Section: Resultsmentioning
confidence: 97%